PRODUCT CHARACTERISTICS THAT INFLUENCE CONSUMER PURCHASING DECISIONS OF SMALL CARS - Yadav, Geeta (International Journal of Research -GRANTHAALAYAH, 2018)
There are multiple factors, specificities, characteristics, circumstances, environment that affect the buying pattern of an individual. A purchase decision is the result of multiple aspects and factors. A motivated person is ready to act according to the perception of the situation (product or services).There are number of product characteristics which should be consider by consumer before purchase .The present paper seeks to identify the factors that influence the consumer behavior with to small cars. The finding of the study can be helpful to marketers in dealing with the customers in a better way.